The shadow challenges to improve the state essential newborn care practices in healthcare providers: evidence from a multicentre cross-sectional study in Ethiopia - Ermias Sisay Chanie; Amare Kassaw; Melkamu Senbeta; Fisha Alebel GebreEyesus; Aragaw Tesfaw; Abenezer Melkie; Tekalign Amera Birlie; Biruk Demissie; Demeke Mesfin Belay; Demewoze Kefale Mekone; Biniam Minuye Birhan; Wubet Alebachew Bayih (BMC, 2021)
Abstract Background Neonatal mortality can be reduced by providing essential newborn care. However, it is overlooked by most healthcare providers in Ethiopia. Hence, this study aims to examine immediate essential newborn care practices and associated factors among healthcare providers in Ethiopia. Methods Institution-based cross-sectional study was conducted among 214 healthcare providers from November 11 to December 19, 2020, at a selected South Gondar health facility. Data were entered into Epi-data 4.2 and then exported to STATA14.0 for analysis. Both bivariable and multivariable logistic regression with a 95% confidence interval were computed. The variable that had a p-value less than 0.25 in bivariable logistic regression was entered into the multivariable logistic regression. In multivariable logistic regression, variables having a p-value < 0.05 were considered a statistically significant association with the poor practice of essential newborn care practice. Results The overall essential newborn care practice among healthcare providers was found to be 74.8% (95% CI: 68.4, 80.2). Diploma educational status (AOR = 7.8, 95% CI:2.80-21.9), presence of workload (AOR = 9.7, 95% CI: 2.76-23.9), unavailability of drugs and vaccines (AOR = 9.8, 95% CI: 6.95-17.7), and having no training (AOR = 3.9, 95% CI: 1.73-8.92) were found to be predictors for poor essential newborn care practices. Conclusion Essential newborn care practice among healthcare providers at South Gondar health institutions was found to be low. Being diploma educational status, presence of workload, unavailability of drugs and vaccines, and having no training were found to be independent predictors for poor practice of essential newborn care. Hence, periodic evaluation and strategies are needed for those predictor variables to address the gaps.